An overview of the Rolls-Royce sCO2-test rig project at Cranfield University - Anselmi Palma, Eduardo; Bunce, Ian; Pachidis, Vassilios; Zachos, Pavlos K.; Johnston, Michael (Southwest Research Institute, 2018)
An experimental facility is currently under development at Cranfield University, aiming to explore supercritical carbon dioxide as a working fluid for future bottoming power cycle applications for Rolls- Royce. The initial objectives of this experimental program are to de-risk and demonstrate the robustness of a closed loop system, as well as to prove the function and performance of individual components and various measurement and control modules. This paper describes the planning and development phases of the test facility and summarises the lessons learnt from the component specification and component interface processes.